The Patients Assessment Chronic Illness Care (PACIC) questionnaire in The Netherlands: a validation study in rural general practice - Hermsen Jan; Jung Hans; van Lieshout Jan; Wensing Michel; Rosemann Thomas (BMC, 2008)
Abstract Background Many patients with chronic illness receive health care in primary care settings, so a challenge is to provide well-structured chronic care in these settings. Our aim was to develop and test a Dutch version of the PACIC questionnaire, a measure for patient reported structured chronic care. Methods Observational study in 165 patients with diabetes or COPD from four general practices (72% response rate). Patients completed a written questionnaire, which included instruments for assessing chronic illness care (PACIC), evaluations of general practice (Europep), enablement (PEI), and individual characteristics. Results The patients had a mean age of 68.0 years and 47% comprised of women. Twenty-two to 35% of responding patients did not provide answers to specific items in the PACIC. In 11 items the lowest answering category was used by 30% or more of the responders and in 6 items the highest answering category was used by this number of responders. Principal factor analysis identified the previously defined five domains reasonably well. Cronbach's alpha per domain varied from 0.71 to 0.83, and the intraclass coefficient from 0.66 to 0.91. Diabetes patients reported higher presence of structured chronic care for 14 out of the 20 PACIC items. The effect of patient evaluations of general practice on the PACIC score was positive (b = 0.72, p < 0.004), but the effect of patient enablement on the PACIC score was negative (b = -1.13, p < 0.000). Conclusion A translated and validated Dutch version of the PACIC questionnaire is now available. Further research on its validity is recommended.